2010
DOI: 10.4236/health.2010.21010
|View full text |Cite
|
Sign up to set email alerts
|

The central nucleus of amygdala is involved in tolerance to the antinociceptive effect of NSAIDs

Abstract: Aim: Repeated microinjections of non-opioid an-algesics into the midbrain periaqueductal gray matter and rostral ventro-medial medulla induce antinociception with development of tolerance. Antinociception following systemic administra-tion of non-steroidal anti-inflammatory drugs (N SAIDs) also exhibit tolerance. Presently our aim was to investigate the development of tolerance to the antinociceptive effects of NSAIDs analgine, ketorolac, and xefocam microinjected into cen-tral nucleus of amygdala (Ce) in rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 18 publications
3
12
0
Order By: Relevance
“…The data reported in this study demonstrate that microinjection of commonly used NSAIDs, diclofenac, ketorolac and xefocam into the rostral part of ACC induces antinociception. These findings are in resemblance with the results of our and other colleagues’ previous investigations in an acute pain model with TF and HP tests, and in which metamizol, xefocam, ketorolac or lysine-acetylsalicylate were given systemically or microinjected into the PAG [ 10 , 11 , 16 – 18 , 25 ], into the CeA [ 13 , 21 ], and the NRM [ 13 , 20 , 26 ]. In the other investigation, responses of spinal dorsal horn wide-dynamic range neurons of rats to mechanical noxious stimulation of a hindpaw were strongly inhibited by intravenous metamizol [ 27 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The data reported in this study demonstrate that microinjection of commonly used NSAIDs, diclofenac, ketorolac and xefocam into the rostral part of ACC induces antinociception. These findings are in resemblance with the results of our and other colleagues’ previous investigations in an acute pain model with TF and HP tests, and in which metamizol, xefocam, ketorolac or lysine-acetylsalicylate were given systemically or microinjected into the PAG [ 10 , 11 , 16 – 18 , 25 ], into the CeA [ 13 , 21 ], and the NRM [ 13 , 20 , 26 ]. In the other investigation, responses of spinal dorsal horn wide-dynamic range neurons of rats to mechanical noxious stimulation of a hindpaw were strongly inhibited by intravenous metamizol [ 27 ].…”
Section: Discussionsupporting
confidence: 89%
“…in juvenile and adult rats in models of acute pain [ 17 , 18 ]. We have also revealed that repeated microinjections of these non-opioids into the dorsal hippocampus (DH), the nucleus raphe magnus (NRM), and the central nucleus of amygdala (CeA), induce antinociception and the effects of tolerance and cross-tolerance to morphine [ 13 , 14 , 19 21 ]. These findings strongly support the suggestion of endogenous opioids involvement in NSAIDs antinociception and tolerance in the descending pain-control system [ 13 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, repeated microinjections of NSAIDs into the DH resulted in a progressive decrease in antinociceptive effectiveness, i.e. induced tolerance similar to that observed with intra-PAG, CeA and NRM injections [ 11 , 12 , 14 - 17 ], and reminiscent of the effect of opiates. For example, it has recently been shown that repeated intrathecal injections of a selective delta opioid receptor (DOPR) agonists deltorphin II or morphine induce tolerance effects on antihyperalgesic and antinociceptive responses in rodents [ 26 ].…”
Section: Discussionmentioning
confidence: 90%
“…In the other experiments in rats, responses of spinal dorsal horn wide-dynamic range neurons to mechanical noxious stimulation of a hindpaw were strongly inhibited by intravenous NSAID dipyrone (metamizole) [30]. Importantly, repeated microinjections of NSAIDs into the DH resulted in a progressive decrease in antinociceptive effectiveness, that is, induced tolerance similar to that observed with intra-PAG, CeA, and NRM injections [16, 17, 1922], and reminiscent of the effect of opiates.…”
Section: Discussionmentioning
confidence: 99%